IMPLEMENTATION OF CONDITIONAL SOCIAL ASSISTANCE PROGRAMS IN IMPROVING THE UTILIZATION OF MATERNAL AND CHILD HEALTH SERVICES IN MANGGAR BARU VILLAGE - Nunik Suciyani; Sri Wahyuni (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to explore in depth the implementation of the Conditional Social Assistance Program in improving the utilization of maternal and child health services in Manggar Baru Village. The main focus of the study is on how the conditions of assistance affect the health behavior of low-income communities. The study uses a descriptive qualitative approach with an interpretive paradigm. The research informants were housewives who were beneficiaries of social assistance, program assistants, and health workers at the Manggar Baru Village Health Center and Integrated Health Service Post. Data were collected through in-depth interviews, participatory observation, and documentation studies, which were then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study show that the conditionality mechanism is effective in increasing health visits because of the link between financial assistance and administrative obligations. The education process through group assistance successfully improved mothers' health literacy regarding nutrition and stunting prevention. However, the surge in visits has not been matched by adequate health infrastructure support, resulting in accessibility constraints in the form of long queues and limited medical personnel.